Global Expressivism: language agency without semantics, reality without metaphysics - Barker, Stephen J ((submitted to) Oxford University Press, 2007)
There is a wide-spread belief amongst theorists of mind and language. This is that in order to understand the relation between language, thought, and reality we need a theory of meaning and content, that is, a normative, formal science of meaning, which is an extension and theoretical deepening of folk ideas about meaning. This book argues that this is false, offering an alternative idea: The form of a theory that illuminates the relation of language, thought, and reality is a theory of language agency. In a nutshell, the theory of language agency is a theory of competence, without being a theory of understanding or grasping rules. It is a theory of cognitive structure and language production. This theory distils all there is to say about language, thought, and reality. It does not supplement a theory of truth-conditions or semantic norms. It is not the explanation of how a speaker, qua cognitive system causally embedded in a larger reality, is able to use a language with some pre-existing semantic characterization. There is no pre-existing semantic characterization. Nevertheless, there are facts of meaning, as good as any other facts. The dissolution of the theory of meaning is accompanied by another disappearance. That is the disappearance of metaphysical questions in a number of domains. Once we complete the theory of language agency, then just as theoretical questions about meaning disappear, certain theoretical questions about existence disappear. Having provided a theory of the language agency for talk of meaning, fact, property, relation, and proposition, there is no question left over about what meanings, facts, properties, relations, and propositions are. There is no theory to be given of their natures. This is not because they have primitive irreducible natures. Rather it is because, in a sense to be clarified in this work, they lack natures. I call this approach to language agency Global Expressivism. That is because it generalizes some of the insights brought to the study of value-language by expressivists. However, it removes these insights from the clouding affects of attempting to make expressivism a semantic theory. Expressivism about value fails as a semantic theory of value talk. However, global expressivism can succeed as a theory of all talk because it is not a semantic theory but a theory of language agency, wherein the theory of meaning is replaced by a theory of talk about meaning.